Desenvolvimento e validação de questionário para investigar a perspectiva de homens sobre a violência contra mulheres perpetrada por parceiro íntimo : Development and validation of questionnaire to investigate men's perspective on violence against women perpetrated by a male intimate partner - Padua, Karla Simonia de, 1968- (2021)
Orientador: Maria José Martins Duarte Osis